Adsorption Equilibrium and Thermodynamic Analysis of CO2 and CH4 on Qinshui Basin Anthracite. (21st December 2019) - Du, Xidong; Wu, Tengfei; Sun, Fulong; Hou, Zhenkun; Liu, Zhenjian; Huo, Liang; Hao, Yu; Zhao, Yuan
Abstract : Adsorption isotherms of CH4 and CO2 on Qinshui Basin anthracite were obtained at the temperatures of 283 K, 303 K, and 323 K using the gravimetric method. The feasibility of the displacement of CH4 by injecting CO2 on this anthracite was verified by calculating the selectivity factor of CO2 over CH4 (α CO 2 / CH 4 ), adsorption affinities, and thermodynamic properties of CH4 and CO2 . Results show that the values of α CO 2 / CH 4 are more than 4.0. Henry's constant (K H ) of CH4 is smaller than that of CO2, and CH4 has a weaker affinity with coal surface. As temperature improves, K H of CO2 and CH4 decrease. Gibbs free energy change (Δ G ) and surface potential (Ω ) of CO2 are more negative than those of CH4, indicating that CO2 adsorption on anthracite is more spontaneous and favorable. The absolute values of Ω and Δ G of CH4 and CO2 increase with pressure rises. Isosteric heat of adsorption (Q st ) of CH4 is lower than that of CO2 . With increasing loading, Q st and entropy loss (Δ S ) of CH4 decrease, while Q st and Δ S of CO2 increase. The higher Δ S of CO2 reveals that the adsorbed CO2 molecules constitute a more stable rearrangement than CH4 molecules. High temperature reduces Δ S of CH4 and CO2 .